Reconstructing Digital Communication Law in Indonesia: Affirming the Right to Information in the Platform Era - Tansah Rahmatullah; Imas Rosidawati Wiradirja; Nugraha Pranadita (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2026)
The rapid expansion of digital platforms has transformed information governance by shifting communication processes from traditional gatekeeping to algorithmically mediated systems. Although Article 28F of the 1945 Constitution guarantees the right to information, Indonesia’s digital regulatory framework has not adequately addressed challenges arising from algorithmic opacity, informational asymmetry, and concentrated platform power. Existing studies primarily focus on data protection, regulatory compliance, and comparative legal reform, while the constitutional implications of platform-based communication remain underexplored. This study aims to reconstruct Indonesia’s digital communication law to strengthen constitutional protection of the right to information in the platform era. Using a doctrinal legal research method, the study applies statutory, conceptual, and comparative approaches to analyze the Electronic Information and Transactions Law, the Personal Data Protection Law, and Ministerial Regulation Number 5 of 2020 as amended by Regulation Number 10 of 2021. The findings reveal four major deficiencies: fragmented regulation, the absence of algorithmic accountability standards, inadequate protection against deceptive digital design practices, and a predominantly command-and-control regulatory paradigm. The study proposes a rights-based reconstruction model grounded in digital constitutionalism, algorithmic accountability, and informational justice.